2014
DOI: 10.1007/s00167-014-2975-8
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and inter-observer reliability of ten major histological scoring systems used for the evaluation of in vivo cartilage repair

Abstract: In expert hands, all the scores showed high intra- and inter-observer reliability, independently of the complexity. Although every score has advantages and disadvantages, ICRSII, O'Driscoll and Modified O'Driscoll scores should be preferred for the evaluation of in vivo cartilage repair in animal models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…We used the histological-histochemical grading system proposed by Mankin et al [ 52 ]. Even though this method is intended to be used for the grading of the human osteoarthritic cartilage, it has also been used in animal studies [ 53 , 54 ]. After 14 days, the samples stored at −70 °C and 4 °C exhibited slightly reduced safranin O staining with diffuse hypercellularity at the superficial cartilage layer and received the scores of 1.83 ± 0.75 and 1.4 ± 0.89, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used the histological-histochemical grading system proposed by Mankin et al [ 52 ]. Even though this method is intended to be used for the grading of the human osteoarthritic cartilage, it has also been used in animal studies [ 53 , 54 ]. After 14 days, the samples stored at −70 °C and 4 °C exhibited slightly reduced safranin O staining with diffuse hypercellularity at the superficial cartilage layer and received the scores of 1.83 ± 0.75 and 1.4 ± 0.89, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other scoring systems commonly used in animal models include O’Driscoll, International Cartilage Repair Society (ICRS and ICRSII), and modified O’Driscol scores [ 189 , 201 , 202 ]. A recent study comparing the various histological scoring systems for OA showed that the ICRSII, O’Driscoll, and modified O’Driscoll scores had higher reliability than other histopathological scores, including the Mankin score [ 203 ].…”
Section: Measures Of Disease Outcomementioning
confidence: 99%
“…We conclude that the DefFill.V is the most important and robust parameter to describe the quality of the repair tissue based on UBM data. This is supported by Bonasia et al who found that the item "overall assessment" of ICRS-II is the most reliable of ten major histopathological classification systems (Bonasia et al, 2015). Furthermore, the comprehensive meta-analysis of Blackman et al (Blackman et al, 2013) revealed that the MOCART item "Degree of defect repair" shows the most significant correlations to clinical outcome measures, and according to Marlovits et al (Marlovits et al, 2006), the MOCART item "Degree of defect repair" also shows the best correlations to patient reported outcomes two years after autologous chondrocyte transplantation.…”
Section: Discussionmentioning
confidence: 60%
“…For cartilage repair outcomes the ICRS recommends the Cartilage Repair Assessment (CRA) scoring system in the ICRS Cartilage Injury Evaluation Package with three distinct categories: "degree of defect repair", "integration to border zone", and "macroscopic appearance". However, intraoperative scoring according to Outerbridge, ICRS, and ICRS-CRA scales involves a large subjective component resulting in high inter-observer variability (Bonasia et al, 2015;Cameron et al, 2003). In addition, macroscopic judgement of the cartilage repair outcome does not allow for assessment of the cartilage thickness unless the bone is exposed.…”
Section: Introductionmentioning
confidence: 99%